Effects of ocean states coupling on the simulated Super Typhoon Megi (2010) in the South China Sea - Zheng, Minglin; Zhang, Ze; Zhang, Weimin; Fan, Maoting; Wang, Huizan (Frontiers in Marine Science, 2023)
Responses of the South China Sea (SCS) to a typhoon are complex due to the susceptible upper layer and active multiscale motions and thus being in urgent need to be resolved and validated in numerical simulations. An atmosphere-ocean-wave coupled model and various in-situ observations were applied to understand the strong interactions between the super typhoon Megi (2010) and the SCS, especially the wave effects on typhoon simulation. In the first group, five sensitive experiments using different combinations of models were conducted and compared to further validate the effectiveness of the ocean coupling. Compared with WRF-only and ROMS-only, results from the coupled experiments evidently improved the accuracy of typhoon intensity, along-track sea surface cooling, currents responses with alternating upwelling and downwelling in the upper layer and significant wave height, but the results are similar between WRF-ROMS and COAWST. To figure out the wave effects, in the second group, six experiments using different surface physical parameterization methods in the MYNN scheme with and without wave effects in the coupled model were conducted. The wave was proved to have positive effect to typhoon through enhanced heat flux and the negative effect through the momentum flux transported into the ocean. Our findings highlight the necessities in using a high-resolution coupled atmosphere-ocean-wave model and use proper surface physical process parameterization to make accurate regional numerical environment predictions.